2021
DOI: 10.4103/jcrt.jcrt_973_19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose intravenous ascorbic acid on cancer patients following ketogenic diet

Abstract: Background: The role of ascorbic acid in cancer therapy is mainly due to its structural similarity with glucose. When supplemented intravenously in high dose, ascorbic acid can get into the cancer cells and induce apoptosis by causing mitochondrial damage. Aim: The aim was to study the efficacy of high-dose intravenous (IV) ascorbic acid as monotherapy in cancer patients following ketogenic diet and its role in improving the quality of life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Studies in adults with cancer using IVC have found reductions in several inflammatory markers, including C-reactive protein, erythrocyte sedimentation rate, 19,20 neutrophil-to-lymphocyte ratio, 21 and F2-isoprostanes. 22 This is particularly important and highlights an indication for use of IVC in cancer settings, given that those with cancer are documented to have increased inflammation.…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in adults with cancer using IVC have found reductions in several inflammatory markers, including C-reactive protein, erythrocyte sedimentation rate, 19,20 neutrophil-to-lymphocyte ratio, 21 and F2-isoprostanes. 22 This is particularly important and highlights an indication for use of IVC in cancer settings, given that those with cancer are documented to have increased inflammation.…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
“…49 The third study used IVC with a ketogenic diet in patients with advanced cancers and noted decreases in inflammatory markers. 20 Due to the multimodal interventions, it is difficult to know what impact IVC had compared with the other treatments.…”
Section: Impact On Quality Of Life and Treatment Toxicitymentioning
confidence: 99%
“…W niszczeniu komórek nowotworowych witamina C wykorzystuje swoje strukturalne podobieństwo w budowie do glukozy. Gdy jest suplementowana dożylnie w dużych dawkach utleniana jest do kwasu dehydroaskorbinowego (DHA), który przechodzi szereg procesów utleniania i redukcji dzięki czemu dochodzi do wzrostu poziomu reaktywnych form tlenu, co przyczynia się do śmierci komórek na drodze apoptozy wywołanej kryzysem energetycznym [15,16]. Omawiane mechanizmy muszą zostać potwierdzone w dobrze kontrolowanych badaniach klinicznych, jednakże odkrycia dotyczące przeciwnowotworowych właściwości witaminy C są wysoce obiecujące i mogą pomóc zidentyfikować grupę chorych , która może odnieść największe korzyści z terapii dużymi dawkami witaminy C, opracować skuteczne strategie łączenia i poprawić ogólny projekt przyszłych badań klinicznych dotyczących witaminy C w różnych typach raka [17,18].…”
Section: Ivc Vit C I Jej Wpływ Na Proces Nowotworowyunclassified
“…Di Tano et al demonstrated that fasting-mimicking diet and VitC treatment exerted a synergistic effect on oxidative damage and chemotherapy-induced cytotoxicity in KRAS-mutant tumors [ 99 ]. In another study, patients who received IVC after ketogenic therapy had increased levels of ketone bodies and reduced generalized inflammation compared to pretreatment [ 98 ]. Despite the encouraging results, the safety of this calorie restriction strategy remains disputable, considering cancer patients often experience malnutrition and increased energy expenditure.…”
Section: Application Of Vitc As a Single Agent Or Adjuvant To Target ...mentioning
confidence: 99%